2014
DOI: 10.1016/j.jsps.2013.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced solubility and intestinal absorption of candesartan cilexetil solid dispersions using everted rat intestinal sacs

Abstract: Naringin, a natural flavonoid, has no undesirable side effects. Therefore, it could be employed as an excipient in the form of solid dispersions to increase CAN intestinal absorption and its oral bioavailability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
39
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 45 publications
7
39
0
1
Order By: Relevance
“…Together, we demonstrated that, improved aqueous solubility followed by effective P-gp efflux pumps inhibition in the GI tract, the CAN oral bioavailability can significantly be enhanced through freeze-dried solid dispersions using naringin, as a novel pharmaceutical excipient (Gurunath et al, 2013(Gurunath et al, , 2014.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Together, we demonstrated that, improved aqueous solubility followed by effective P-gp efflux pumps inhibition in the GI tract, the CAN oral bioavailability can significantly be enhanced through freeze-dried solid dispersions using naringin, as a novel pharmaceutical excipient (Gurunath et al, 2013(Gurunath et al, , 2014.…”
Section: Introductionmentioning
confidence: 91%
“…In these dispersions, the drug is often present as partially amorphous or amorphous substance (Yonemochi et al, 1997(Yonemochi et al, , 1999Mura et al, 2002;Dai et al, 2007). Previously, we reported that freeze-drying is the most suitable preparative technique among various pharmaceutical interventions for preparing amorphous solid dispersions of poorly water-soluble drug, CAN (Gurunath et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The dissolution studies for the cocrystals can be done within the suitable dissolution medium described in drug protocol of referred pharmacopoeia. The drug samples can be collected in the suitable quantity at predetermined time interval and can be examined with the help of suitable means like HPLC or UV [113,114] .…”
Section: Evaluation Of Cocrystalsmentioning
confidence: 99%
“…The various tested concentrations of naringenin selected in this study were based on our previously published reports (Gurunath et al, 2013a(Gurunath et al, , 2013b wherein we demonstrated that naringin at 15 mg/kg was noticed to significantly inhibit the P-gp in the intestine, thus facilitating the intestinal absorption and oral bioavailability of P-gp substrate, when formulated in solid dispersions. This was also supported by other authors using naringenin as P-gp inhibitor in their research work, although with a different P-gp substrate (Surya Sandeep et al, 2013).…”
Section: +mentioning
confidence: 99%
“…Such bioflavonoids, naringin or naringenin show inhibition of P-gp-mediated cellular efflux of P-gp substrates, which implies that they might affect the absorption, distribution and elimination of P-gp substrates, with increase in intestinal absorption and oral bioavailability (Lassoued et al, 2011;Gurunath et al, 2013b).…”
mentioning
confidence: 99%